ESTIMATION OF MAIZE BIOMASS USING UNMANNED AERIAL VEHICLES - Calou,Vinícius B. C. (2019)
ABSTRACT Unmanned aerial vehicles (UAVs) are a promising tool for technology development and transfer and for the economic success of the agricultural sector. The objective of this study is to assess the validity of biomass estimation in a commercial maize plantation using aerial images obtained by a UAV. The proposed methodology involved analyzing images acquired in scheduled flights, processing orthophoto (georeferenced image) data, evaluating digital terrain elevation models, and assessing the quality of dense point clouds. Data were collected using two cameras, one with a 16-megapixel flat lens and the other with a 12-megapixel fish-eye lens coupled to a UAV, at two flight altitudes (30 and 60 meters) over hybrid maize (AG1051) crop irrigated by center pivot in the municipality of Limoeiro do Norte, Ceará, Brazil. Crop biomass was estimated in 1 m2 plots sampled randomly, and data were validated by interpreting aerial images of target areas. The measurements of biomass using UAV-based aerial images were promising. The estimated values were more accurate using the fish-eye lens at 30 m altitude, corresponding to 2.97 kg m-2, which is very close to the values measured in the field (2.92 kg m-2).